Green Tea: Flavor characteristics of a wide range of teas including brewing, processing, and storage variations and consumer acceptance of teas in three countries - Lee, Jeehyun (Kansas State University, 2009)
A green tea descriptive sensory lexicon was developed by a highly trained panel, which identified, defined, and referenced 31 flavor attributes of green tea. The attributes were categorized as “green” (asparagus, beany, Brussels sprout, celery, parsley, spinach, green beans, and green herb-like), “brown” (ashy/sooty, brown spice, burnt/scorched, nutty, and tobacco), “fruity/floral” (fruity, floral/perfumy, citrus, and fermented), “mouthfeel” (astringent and tooth-etching), “basic tastes” (overall sweet and bitter), and other attributes (almond, animalic, grain, musty/new leather, mint, seaweed, and straw-like). Using the green tea lexicon, the flavor differences that exist among a wide range of green teas (n=138) produced in various countries were determined. Roast-processed teas were mostly responsible for brown-related flavors and steam-processed teas were mostly responsible for green-related flavors. Aroma analyses of green tea showed that the concentration of volatile compounds were much lower than stated in the literature. Brown, brown-related attributes, bitterness, and astringency became stronger and green and green-related attributes become weaker as the brewing time lengthened (1, 2, 5, and 20 min) and the water temperature increased (50, 70, 95°C). The flavor characteristics of roast-processed, steam processed, or roast-steam-processed Korean green teas differed only in their characterizing green flavors. The flavor and aroma of green teas change after sequential brewings. Green teas in leaf form can be brewed four times: the first two brews providing stronger flavor and aroma characteristics whereas the third and fourth brews will provide milder flavor and aroma characteristics. The flavor and aroma change in green teas that are stored over two years were observed at 3, 6, 12, 18, and 24 months after their original packaging dates. Green tea changes minimally during the first year of storage and only slightly more during the first two years of storage. Consumer studies and descriptive evaluations were conducted to understand what green tea flavor characteristics influence US consumers' liking. Twelve green tea samples were evaluated by three consumer groups from Korea, Thailand, and the United States. The current research suggests that familiarity plays a role in tea acceptance. However, various flavor profiles may be acceptable to consumers who are familiar with other flavors of green tea.
Keywords: green tea; descriptive sensory analysis; consumer acceptability; volatile compounds; Agriculture, Food Science and Technology (0359)